Kepatuhan Hukum PMI dan P3MI Studi Kasus Penempatan Ilegal Pekerja Migran dari Lombok ke Malaysia - Anisa Seftiani Mahmud; Arnold Daud; Nova Septiani Tomayahu (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to analyze the legal compliance of Indonesian Migrant Workers (PMI) and Indonesian Migrant Worker Placement Companies (P3MI) in cases of illegal placement from Lombok to Malaysia. The approach used is juridical-normative by examining relevant laws and regulations and secondary data from actual cases. The results of the study indicate that the level of legal compliance of PMI and P3MI is weak because there have been violations of legal procedures both by PMI who depart without official documents and P3MI who are indicated to be working with brokers or unofficial agents to expedite departure without procedures. Due to the weak level of legal compliance of PMI and P3MI, BP2MI assesses this as a violation in the form of illegal placement which causes the Malaysian government to carry out mass deportation of migrant workers. This study concludes that efforts to improve legal compliance require strengthening regulations, increasing legal literacy for prospective PMI, and strict supervision of P3MI performance in the process of placing workers abroad.